2014
DOI: 10.1186/s13223-014-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between allergy and asthma control, quality of life, and emotional status in patients with asthma: a cross-sectional study

Abstract: BackgroundPsychiatric comorbidities are prevalent in patients with chronic somatic disorders such as asthma. But, there is no clear evidence regarding the effect of atopic status and the type of sensitized allergen on emotional status. The aim of the present study was to investigate the effects of house dust mites and pollen allergies on emotional status, asthma control and the quality of life in patients with atopic asthma.MethodsThe study included 174 consecutive patients who were diagnosed with asthma accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
4
30
0
11
Order By: Relevance
“…Cooper et al showed that, the prevalence of anxiety was 47.3%, depression was in 22.3% in asthmatic patients (18). Another study in Turkey, revealed that 33.3% had anxiety, and 47.7% had depression in asthmatic patients (19). Our study results are consistent with those findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Cooper et al showed that, the prevalence of anxiety was 47.3%, depression was in 22.3% in asthmatic patients (18). Another study in Turkey, revealed that 33.3% had anxiety, and 47.7% had depression in asthmatic patients (19). Our study results are consistent with those findings.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies examining the association between asthma severity and depression have suggested that positive association (19)(20)(21). In another study, anxiety and depression were more frequent among patients with "difficult" asthma (5).…”
Section: Discussionmentioning
confidence: 94%
“…Problems with depression in patients with bronchial asthma have been reported in the literature (20). Depression plays a major role in children's internalizing disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Atopinių ligų ir emocinės disfunkcijos sąsajas skirtingo amžiaus vaikų grupėse patvirtina dauguma tyrimų: ikimokykliniame amžiuje, viduriniojoje vaikystėje, taip pat ir paauglystėje atskleidžiamos sąsajos su miego sutrikimais, aukštesniu depresiškumo ir nerimo lygiu [34,35,37,38].…”
Section: Atopiniu Dermatitu Sergančio Vaiko Emocinio Funkcionavimo Ypunclassified
“…Tačiau pati liga taip pat veikia asmens emocinę būseną bei per įtampos išgyvenimą atsiliepia artimiems santykiams [9,24,26,38]. Atsižvelgiant į įvairiapusiškas sąsajas, būtų svarbu pamėginti atskleisti vidinius, psichikoje vykstančius procesus.…”
Section: Atopinis Dermatitas Ir Emocinių Sunkumų Formavimasisunclassified